Somatotopic Arrangement of the Human Primary Somatosensory Cortex Derived From Functional Magnetic Resonance Imaging - Willoughby, W. R.; Thoenes, Kristina; Bolding, Mark (Frontiers in Neuroscience, 2021)
Functional magnetic resonance imaging (fMRI) was used to estimate neuronal activity in the primary somatosensory cortex of six participants undergoing cutaneous tactile stimulation on skin areas spread across the entire body. Differences between the accepted somatotopic maps derived from Penfield's work and those generated by this fMRI study were sought, including representational transpositions or replications across the cortex. MR-safe pneumatic devices mimicking the action of a Wartenberg wheel supplied touch stimuli in eight areas. Seven were on the left side of the body: foot, lower and upper leg, trunk beneath ribcage, anterior forearm, middle fingertip, and neck above the collarbone. The eighth area was the glabella. Activation magnitude was estimated as the maximum cross-correlation coefficient at a certain phase shift between ideal time series and measured blood oxygen level dependent (BOLD) time courses on the cortical surface. Maximally correlated clusters associated with each cutaneous area were calculated, and cortical magnification factors were estimated. Activity correlated to lower limb stimulation was observed in the paracentral lobule and superomedial postcentral region. Correlations to upper extremity stimulation were observed in the postcentral area adjacent to the motor hand knob. Activity correlated to trunk, face and neck stimulation was localized in the superomedial one-third of the postcentral region, which differed from Penfield's cortical homunculus.